Meta-Analysis: The Effect of Discovery Learning On Students' Creative Thinking Abilities - Syafrial, Syafrial; Pairin, Pairin (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
The discovery learning model has been widely applied in the learning process at all levels of education. However, it is not known how effective the discovery learning model is on creative thinking abilities, especially science subjects at the senior high school level. The aim of this research is to describe how meta-analysis of the discovery learning model affects students' creative thinking abilities in science subject matter (Physics, Chemistry, Biology). The research method used is descriptive in the form of survey research using a meta-analysis design, namely by re-analyzing the results of scientific publications in the form of research articles, theses and theses. The data analysis technique used is effect size analysis using the Glass formula. The results of data analysis show that the average effect size of all publication results is 0.79 in the high category with an average effect of 78.81%. Based on the relationships between the variables obtained, learning using the discovery learning model to improve creative thinking skills is best applied to Biology subjects, the effect size is 0.95 in the high category and has an influence of 83%. Based on the subject group, the influence of discovery learning to improve students' creative thinking abilities in Biology subjects is 83%, while in Chemistry subjects it is 73.2%, and in Physics subjects it is 71.4%. In the future, it is hoped that the results of this research can become a reference for reviewing applications. discovery learning to improve students' creative thinking abilities in science learning